Clinical Effect of MOTOmed Intelligent Motion Feedback Training Combined with Refined Rehabilitation Training on Patients with Hemiplegia after Cerebral Infarction - WANG Bin; GAO Songnian; LIU Qiaoyun; DONG Xinchun (康复学报)
ObjectiveTo observe the clinical effect of MOTOmed intelligent motion feedback training combined with refined rehabilitation training on neurological function, balance function, limb motor function and quality of life of patients with hemiplegia after cerebral infarction.MethodsA total of 148 patients with hemiplegia after cerebral infarction in the rehabilitation center of Nantong Third People's Hospital from January to October 2022 were randomly divided into control group and observation group, with 74 cases in each group. The control group received refined rehabilitation training in addition to the routine treatment. According to the degree of limb motor dysfunction (bedridden, sit upright, stand upright with assistive devices, and stand upright without assistive devices), the patients with hemiplegia after cerebral infarction were provided with corresponding exercise rehabilitation training (such as limb joint training, body transfer training, balance training and walking training) five days a week for 12 weeks. The observation group received MOTOmed intelligent motion feedback training in addition to the training of the control group (upper/lower limb motor rehabilitation training with passive movement, assistive movement and active training modes), once a day, 45 minutes a time, five days a week for 12 weeks. Before and after treatment, the National Institutes of Health stroke scale (NIHSS) score was used to evaluate the neurological deficits. Berg balance scale (BBS) was used to evaluate balance function. Fugl-Meyer assessment (FMA) scale was used to evaluate limb motor function; modified Barthel index (MBI) was used to evaluate activities of daily living. The world health organization quality of life-BREF (WHOQOL-BREF) scale was used to evaluate quality of life. Blood flow velocity changes of the middle cerebral artery (MCA) and anterior cerebral artery (ACA), levels of serum nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) were compared.ResultsCompared with that before treatment, NIHSS score of the control group and the observation group after treatment decreased significantly, while FMA score of the upper or lower limbs, BBS score, MBI score, WHOQOL-BREF score, MAC and ACA blood flow velocity and serum NGF and BDNF level increased significantly, and the differences were statistically significant (P<0.05). Compared with the control group, NIHSS score of the observation group after treatment was lower, while FMA score of the upper or lower limbs, BBS score, MBI score, WHOQOL-BREF score, MAC and ACA blood flow velocity and serum NGF and BDNF level were higher, and the differences were statistically significant (P<0.05).ConclusionMOTOmed intelligent motion feedback training combined with refined rehabilitation training can improve neurological function, balance function, limb motor function and quality of life of patients with hemiplegia after cerebral infarction, which is recommended for clinical application.